1996 Kansas Performance Tests with Winter Wheat Varieties - Roozeboom, Kraig L. (Kansas State University. Agricultural Experiment Station, 2013)
The Kansas Agricultural Experiment Station annually compares both new and currently grown varieties in the state’s major crop-producing areas. These performance tests generate unbiased performance information designed to help Kansas growers select wheat varieties suited for their area and conditions.
Keywords: Wheat; Crop development; Diseases; Weather; Insects; Statistics; Kansas